Kebijakan Internal Madrasah Dalam Meningkatkan Mutu Pendidikan Di MI Nurul Ummah Kotagede Yogyakarta - Muhammad Alfiansyah; Muhammad Shaleh Assingkily; Andi Prastowo (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2020)
Abstract This research describes several management of MI Nurul Ummah in order to improve the quality of education in the school, the type of research in this paper is descriptive qualitative. Data collection techniques used by interview and also with various sources both from relevant books and journals. From the results of the writing, it is known that there are some policies implemented by MI Nurul Ummah management (1) Assisting the reading of Asmaul Husna, intends to educate students characters to love Allah through Asmaul Husna, (2) The implementation of Full Day School, the application of this policy is expected to make it easier to supervise students in the school, (3) Dhuha prayer in congregation, get children to pray in congregation and a good character building, (4) The training of teachers to upgrade teachers knowledge in order to produce a good quality of education. While that which is the inhibiting factors of the policy namely internal factors (Funds, Teachers, Students) external factors (Parents of Students, Society)